The magnetic properties of Fe-Al-Nb intermetallic compounds - Imaizumi, Momotaro [UNESP]; Laks, Bernardo; Bejerano, Jose M. Zalaya; Gama, Sergio; Coelho, Adelino A.; Mota, Marilza A.; Caram, Rubens (My University, 2002)
The magnetic properties of Fe-Al-Nb intermetallic compounds were discussed. The magnetic behavior was studied using the linearized plane wave method. The Fe-Al-Nb alloys were simulated by the Fe substitution for Al atoms in the (0,0,0) and (0,0,5) sites of the Fe2Nb phase. The spin magnetic moments were 1.53 μB for the Fe atom in the site with 6 Fe neighbors, -0.012 μB for the Al atom with 2 Al neighbors and -0.048 μB for the Nb atom with 4 Nb neighbors.